The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1097/01.tp.0000209596.01164.c9
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Perceived Health Status in Patients after Kidney Transplantation

Abstract: Major differences exist in PHS among kidney transplant recipients depending on their age. Side effects of therapy are the most important predictor of PHS for all age groups. PHS of young patients mostly depends on their renal function and their social support. Education and working activities are most important for middle-aged people whereas in older patients PHS is mostly affected by comorbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

2008
2008
2011
2011

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 22 publications
1
23
0
1
Order By: Relevance
“…Better HRQOL scores in kidney transplant recipients have been previously associated with younger age, male gender, Caucasian race/ethnicity, Tacrolimus-based versus Cyclosporin-based immunosuppression, simultaneous kidney/ pancreas transplant in diabetic patients with ESRD, lower number and less severe comorbidities, no complication after transplant surgery, lesser time since kidney transplant, and absence of or mild complications of immunosuppression versus severe complications [46][47][48][49][50][51][52]. Consistent to previous findings, our data show that poorer socioeconomic status [13] was associated with lower quality of life independent of health status indicators.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Better HRQOL scores in kidney transplant recipients have been previously associated with younger age, male gender, Caucasian race/ethnicity, Tacrolimus-based versus Cyclosporin-based immunosuppression, simultaneous kidney/ pancreas transplant in diabetic patients with ESRD, lower number and less severe comorbidities, no complication after transplant surgery, lesser time since kidney transplant, and absence of or mild complications of immunosuppression versus severe complications [46][47][48][49][50][51][52]. Consistent to previous findings, our data show that poorer socioeconomic status [13] was associated with lower quality of life independent of health status indicators.…”
Section: Discussionmentioning
confidence: 98%
“…To further explore the association of CKD severity with HRQOL, we specified few secondary analyses. Since it has been reported that patient age and gender may influence the adjustment process to chronic illnesses [27][28][29][30], we tested whether the association between selfreported outcomes and CKD severity was statistically different across demographic strata by adding the appropriate interaction term in the model. At every step, we included only variables selected with stepwise method (entry level.…”
Section: Discussionmentioning
confidence: 99%
“…The physical restrictions are associated, mostly, to the frequent occurrence of comorbidity and side effects of the immunosuppressive therapy. The presence of comorbidity [21][22][23][24][25][26][27][28] has been considered as a predictor of worse quality of life after renal transplantation, particularly diabetes [29,30], although the quality of life of the diabetic patient submitted to dialysis improves after transplantation [1]. Besides the patients with diabetes previous to transplantation, up to 25% of all graft recipients at 3 years posttransplant have new-onset diabetes, as a side effect of the immunosuppressive drugs [31].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have consistently shown that social support may be a major factor in adaptation to physical illness and positive social interaction is associated with better physical functioning [26,[29][30][31][32].…”
Section: Social Support and Perceived Physical Health Statusmentioning
confidence: 99%